Association between dietary total antioxidant capacity and hypertension in Iranian Kurdish women - Hawal Lateef Fateh; Narmin Mirzaei; Mohammed Ibrahim Mohialdeen Gubari; Mitra Darbandi; Farid Najafi; Yahya Pasdar (BMC, 2022)
Abstract Background Antioxidants intake from diet has been identified as one of the effective factors in the development of hypertension (HTN). The present study aimed to investigate the association between total antioxidant capacity (TAC) and HTN in women. Methods This cross-sectional study was performed using the baseline phase data of the ravansar non-communicable disease cohort study. The TAC was calculated using food items of the food frequency questionnaire. TAC scores were classified into four groups (quartile). The first and fourth quartiles had the lowest and highest TAC scores, respectively. Logistic regression analysis was utilized to estimate the odds ratio. Results A total of 5067 women were included in the study. Women with the highest socioeconomic status (SES) had a significantly higher TAC intake compared to those with the lowest SES (P < 0.001). The participants in the third and fourth quartiles of the TAC had significantly lower odds of HTN, respectively by 21% (OR = 0.79; 95% CI: 0.64, 0.972) and 26% (OR = 0.74; 95% CI: 0.60, 0.91), compared to the first quartile. After adjusting for confounding variables was found to significantly reduce the odds of developing HTN in the fourth quartile of TAC by 22% compared to the first quartile (OR = 0.78; 95% CI: 0.62, 0.97). Conclusion A high dietary TAC was associated to a decreased odd of HTN in women. We could suggest a diet rich in natural antioxidants as it may help prevent development of HTN.